Plant spacing and weeding regime interaction in transplant aus rice - Malek, Md Abdul; Harun-Or-Rashid, A K M; Sarker, Uttam Kumer; Sarkar, Shubroto Kumar; Islam, Md Anwarul (Fundamental and Applied Agriculture, 2016)
Spacing is one of the determinants of crop growth and development while weed is a limiting factor. Optimum spacing and proper weed management greatly facilitate the growth and yield of rice. A field experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to study the interaction of spacing and weeding regime on the performance of transplant aus rice cv. BR26 (Shraboni). The experiment comprised four spacing viz. 25cm×15cm,20cm×15cm,15cm ×10cm,10cm×10cm and five weeding regimes viz. no weeding, one weeding (at 15 DAT), one weeding (at 25 DAT), two weeding (at 15 and 30 DAT) and two weeding (at 20 and 40 DAT). The experiment was laid out in a randomized complete block design with three replications. Plant spacing and weeding regime greatly influenced the performance of aus rice. the highest number of effective tillers hill-1 (9.47) and grains panicle-1 (98.27) were recorded from 20 cm × 15 cm spacing which in consequence resulted in the highest grain yield (4.20 t ha-1). The lowest number of effective tillers hill-1 (4.31), grains panicle-1 (87.07), grain yield (2.86 t ha-1) were recorded from 10 cm × 10 cm spacing. The highest number of total tillers hill-1 (13.52), effective tillers hill-1(10.95), grains panicle-1 (103.30) and grain yield (4.48 t ha-1) were found from two weeding done at 15 and 30 DATs. The interaction of 20 cm × 15 cm spacing and two weeding at 15 and 30 DATs gave the highest number of total tillers hill-1 (16.33), effective tillers hill-1 (13.77), grains panicle-1 (105.00) and grain yield (5.23 t ha-1) . The lowest grain yield (2.24 t ha-1) was recorded from the interaction of 10 cm × 10 cm spacing with no weeding. Aus rice cv. BR26 (Shraboni) may be cultivated following 20 cm × 15 cm spacing along with two weeding at 15 and 30 DATs to ensure higher yield.